2014
DOI: 10.1111/1365-2664.12271
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pathways for managing multiple disturbances to limit plant invasions

Abstract: Summary1. Plant invasions are predicted to accelerate in a world with increased anthropogenic disturbance. Non-native species pre-adapted to these disturbances may especially be poised to invade novel communities. Conservation managers therefore need predictions of how to alter disturbances to maximize the persistence of native biodiversity. 2. We tested a multivariate hypothesis about the causal mechanisms underlying plant invasions in an ephemeral wetland in South Island, New Zealand, to inform management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…In contrast to our findings, Tanentzap et al (2014)emphasised the importance of intensive disturbance regimes over intermediate ones in reducing invasion; we argue that the failure to substantially increase diversity and the associated increased potential for facilitating secondary invasion may outweigh the benefits gained by dramatically reducing the invaders’ abundance. In contrast to intensive treatments, management types with intermediate intensity have balanced effects: they decrease the invader's fitness, while potentially increasing the diversity of communities, which can be more effective for further sustainability in the invaded communities.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Tanentzap et al (2014)emphasised the importance of intensive disturbance regimes over intermediate ones in reducing invasion; we argue that the failure to substantially increase diversity and the associated increased potential for facilitating secondary invasion may outweigh the benefits gained by dramatically reducing the invaders’ abundance. In contrast to intensive treatments, management types with intermediate intensity have balanced effects: they decrease the invader's fitness, while potentially increasing the diversity of communities, which can be more effective for further sustainability in the invaded communities.…”
Section: Discussioncontrasting
confidence: 99%
“…Vernal pool ecosystems rely heavily on winter precipitation, experience relatively shallow inundation depths, and are attune to small variations in depth and duration (Holland & Jain ; Emery et al ; Gosejohan et al ) as well as inundation timing (Kneitel ). These inundation subtleties within the pool boundaries have been shown to exclude invasion by a number of species that are not adapted to such extreme conditions (Gerhardt & Collinge ; Tanentzap et al ). Our study demonstrated that the invasive pools contained the shallowest inundation depths regardless of variations in year.…”
Section: Discussionmentioning
confidence: 99%
“…A high groundwater table in the spring and in the first part of summer is a major disturbance factor in wet meadows. Maintenance of the hydrological and nutrient regimes of ephemeral wetlands limits the number of introduced species (Tanentzap et al, 2014). Adequate rewetting is necessary for the successful restoration of wetlands (Ramseier, Klötzli, Bollens, & Pfadenhauer, 2009).…”
Section: Vegetationmentioning
confidence: 99%